OBESITY, HYPERTENSION AND CYCLE OF POVERTY IN URBAN POOR SOCIETY - Eka Fitria (Aceh International Journal of Social Science, 2014)
Abstract: This paper is about to prove that hypertension has been becoming as a major health problem among the working-aged population in Aceh’s urban area, defined as those 18-64 years old. The employed procedures are pursuant to ethical standards of National Institute of Health Research and Development, Indonesia Ministry of Health. This research is conducted from April 2012 to November 2012 as a cross-sectional study with purposive sampling scheme in urban areas of Gampong Ceurih, Ulee Kareeng sub-district of Banda Aceh, Indonesian’s province of Aceh. The inclusion criterions for the participants in this study are: 1) Married 2) categorized as poor people based on standard of Central Bureau of Statistic (BPS). Logistic regression with bivariate and multivariate analysis is employed to scrutinize linkage between several individual characteristics and hypertension. Bi-variate logistic regression confirms that age group, educational backgrounds, employment and housing status as well as obesity are statistically significant to hypertension stage-1; moreover, the probability of hypertension stage-1 increases progressively with increasing age and BMI. Multivariate logistic regression confirms that the individual characteristics of the poor those are significantly determining hypertension only age group and BMI class. For normal weight (BMI 25), the probability to get hypertension stage-1 at aged 18-30, 31-42, and 43-54 years are 7.05%, 25.36%, and 70.53%, respectively. For the obese (BMI ≥30), the probability to get hypertension stage-1 at aged 18-30, 31-42, and 43-54 years are respectively 36.18%, 71.76%, and 94.71%. This evidence implies that hypertension is a common health problem of the poor at elderly population. In short, government intervention should not only deal with curative aspect such as enforcing universal health coverage program to entire population in Aceh because this program may be ineffective to maintain health of the poor if the healthy foods are still hard to be obtained by poor families. Key Words: Health Problem, Aceh, Poverty Issues